2005
DOI: 10.1111/j.1469-0691.2005.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of rifampicin and ciprofloxacin combination therapy after surgical debridement in the treatment of early manifestation prosthetic joint infections

Abstract: Prosthetic joint infections are difficult to eradicate, and antibiotic and surgical treatment strategies lack standardisation. The present study followed 29 patients (median age 72 years, median American Society of Anesthesia score of two) with early prosthetic joint infections. Treatment consisted of device retention, surgical debridement and therapy with rifampicin and ciprofloxacin for 3 months. This treatment regimen failed in five patients during the study, with a median observation period of 674 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 13 publications
3
58
0
4
Order By: Relevance
“…Duration from symptom onset has similarly been reported as the most important prognostic factor for infection control in a number of studies [3,6,17,19]. For instance, Crockarell et al [11] suggested débridement and retention of prosthesis have been successful when treatment was commenced within 6 days of symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duration from symptom onset has similarly been reported as the most important prognostic factor for infection control in a number of studies [3,6,17,19]. For instance, Crockarell et al [11] suggested débridement and retention of prosthesis have been successful when treatment was commenced within 6 days of symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options available include débridement with retention of components [3,6,17,19], single-stage revision [20,36], twostage revision and multistage revision [24], long-term suppressive antibiotics, and salvage procedures [36].…”
Section: Introductionmentioning
confidence: 99%
“…Barberan'ın yaptığı bir prospektif kohort çalışmada ise semptom süresi < 1 ay olan hastalarda, levofloksasin + rifampisin kombinasyonu ile bakteriyolojik ve klinik başarı oranı %69.5-80 olarak tespit edilmiştir [25] . Rifampisinin kinolonlarla (siprofloksasin ve levofloksasin) kombinasyon tedavilerinin incelendiği dört çalışmada da %65-100 başarı oranları tespit edilmiştir [24][25][26][27][28] . Bizim çalışmada da siprofloksasin + rifampisin tercih edilen kombinasyonlar arasında yer almaktadır.…”
Section: Tablo 4 Operasyon Sonrası Metisiline Dirençliunclassified
“…Rifampin is thought to penetrate the biofilm, and is recommended in all cases of Staphylococcal PJI treated with DAIR [1,2] . Several studies describe the success rates of a regimen including rifampin [15,[69][70][71] , but only one prospective clinical study has been performed, which also observed higher success rates when rifampin was added to the antibiotic regimen [72] . Another, more recent study, compared a prospective rifampin group with a retrospective rifampin and a retrospective non-rifampin group [73] .…”
Section: Systemic Antibiotic Treatmentmentioning
confidence: 99%